Non-palm Plant Volatile α-Pinene Is Detected by Antenna-Biased Expressed Odorant Receptor 6 in the Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) - Ji, Tianliang; Xu, Zhi; Jia, Qingchen; Wang, Guirong; Hou, Youming (Frontiers in Physiology, 2021)
The majority of insects rely on highly complex and precise olfactory system to detect various of volatile organic compounds released by host and non-host plants in environments. The odorant receptors (ORs) are thought to play an important role in odor recognition and the molecular basis of odorant receptors, particularly in coleopterans is relatively poorly understood. The red palm weevil (RPW), Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) is one of the most destructive pests of global palm-industry. Although, feeding and egg-oviposition behaviors of RPW can be repelled by some non-palm plant volatiles, such as 𝛼-pinene, geraniol or 1-octen-3-ol, there is limited understanding on how RPW recognize non-host plant volatiles. Here, three candidate RferORs were identified from Rfer-specific clade and tissue expression analysis showed were mainly expressed in the antennae of both sexes. Functional characterization of RferOR6, 40 and 87 were analyzed by using the Xenopus oocyte expression system and results indicated that RferOR6/RferOrco was narrowly tuned to 𝛼-pinene. In conclusion, our study reveal that RferOR6 is an antennae-biased expressed odorant receptor used by RPW to detect non-palm plants volatile compound 𝛼-pinene and based on the function of RferOR6 lay a foundation for further functional studies of other OR genes.